Optimization of reinforced ring base depth for vertical shaft sinking in soft soil using VSM method - Dhyaa A.H. Abualghethe; Baogang Mu; Guoliang Dai; Sijin Liu; Zhongwei Li; Songyu Liu; Lei Han (Underground Space)
Constructing vertical shafts in densely populated urban areas with complex geological conditions poses significant challenges, necessitating innovative construction techniques and design optimization. This study investigates the deformation behavior of a 42.5 m deep shaft excavated using the vertical shaft sinking machine (VSM) method in Shanghai’s soft soil conditions comprising deep cohesive soil layers. Comprehensive numerical analysis simulated the VSM construction process, analysing deformations within the shaft structure, surrounding soil, and adjacent buildings while evaluating the influence of varying reinforced ring base depths. Results reveal a significant 30% reduction in the maximum lateral shaft deformation, from 28 to 20 mm, by increasing the reinforced ring base depth to an optimal 16 m, enhancing lateral stability. Vertical deformations exhibited complex settlement and uplift mechanisms in segmental rings and piles, influenced by factors like excavation stages, pile installation, water pressures, and adjacent loads. The optimal 16 m depth effectively mitigated uplift, and optimized load distribution, limiting the maximum settlement to 12 mm while minimizing dewatering-induced uplift effects. Analysis indicated reduced lateral movements and settlements in surrounding buildings with increasing distance from excavation, highlighting VSM’s potential for minimizing impacts on neighboring structures. This study emphasizes VSM’s suitability for shaft projects in geologically complex areas, providing insights for design, mitigating environmental impacts, and enhancing deep excavation safety and efficiency in soft soils. The findings contribute to optimizing vertical shaft construction, ensuring successful underground infrastructure execution in challenging conditions. Identifying the optimal reinforced ring base depth promotes sustainable urban development by minimizing disturbances. This research advances innovative methods and strategies for complex underground projects.